The Fair Use Sermon: When Verbal And Visual Borrowing Cross The Line (Homiletic, 2022)
This paper hopes to add to the conversation regarding plagiarism by approaching this issue from a different angle, primarily in regards to how we should properly use (and cite) sources that fall more into the realm of fair copyright usage. We live in a what has been called a wired world, meaning that we who speak for God must practice integrity in all aspects of our teaching ministry—including our creative aspects, such as audio, video and visual imagery. This paper, then, will discuss this concern, looking first at the problem of both verbal and visual borrowing, then provide an explanation of fair use codes, and then conclude with a discussion of existing and creative solutions especially as they relate to visual borrowing.